1995
DOI: 10.1117/12.209190
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 64-Mb DRAM using x-ray lithography

Abstract: This paper describes results achieved from the fabrication of 64Mb DRAM chips using x-ray lithography for the gate level. Three lots were split at the gate level for exposure with either Micrascan 92 at IBM's Advanced Semiconductor Technology Center (ASTC) or x-ray at the Advanced Lithography Facility (ALF) containing a Helios superconducting storage ring and a Suss stepper. The x-ray mask was fabricated at MMD (Microlithographic Mask Development Facility) as a two-chip mask containing one chip which had zero … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…3. Results and discussion 3-1 Intra-wafer CD variation Figure 2 shows cross-sectional images of the three types of 130-nm patterns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Results and discussion 3-1 Intra-wafer CD variation Figure 2 shows cross-sectional images of the three types of 130-nm patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Proximity x-ray lithography (PXL) is one of the most promising candidates for next-generation lithography because of its high potential regarding resolution, CD control, process margin, throughput, and so on. Several studies on CD control in PXL have been reported [1][2][3][4]. One of them reported that the total CD variation for 140-nm line-andspace (L/S) patterns was 19.5 nm, with the main causes being a mask-CD variation of 15 nm (36) and instability in the exposure dose [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no optical lens makes SR lithography available for a larger exposure field. As SR lithography has these excellent features, many researchers study SR lithography aggressively [2,3], and demonstrate its high performance [4] and applicability of device fabrication [5][6][7][8][9]. In this work, we applied SR lithography to fabricate 0.14µm level device structure (giga bit level DRAM) and evaluated its replicating performance on the topographic structure.…”
Section: Introductionmentioning
confidence: 99%